Ankyrin repeat domain 1: A novel gene for cardiac septal defects. (19th February 2019) - Yang, Yongchao; Xia, Yu; Wu, Yueheng; Huang, Shufang; Teng, Yun; Liu, Xiaobing; Li, Ping; Chen, Jimei; Zhuang, Jian
Abstract: Introduction: Cardiac septal defects account for more than 50% of congenital heart defects. Ankyrin repeat domain 1 ( ANKRD1 ) is an important transcription factor that is mutated in multiple cardiac diseases; however, a relationship between the ANKRD1 mutation and cardiac septal defects has not been described. Methods: We examined genetic mutations in a large family with three cardiac septal defect patients. Whole exome sequencing, bioinformatics and conservation analysis were utilized to predict the pathogenicity of candidate mutations. Dual luciferase reporter assay and nuclear localization experiments were performed to evaluate the influence of target mutation. Results: A heterozygous, missense variant of ANKRD1 (MIM* 609599): NM_014391: exon6: c.C560T:p.S187F was identified at a highly conserved region. Sanger sequencing in extended family members demonstrated an incomplete inheritance model. When co‐activated with NKX2.5, ANKRD1 repressed ANF expression as assessed by a dual‐luciferase reporter assay, and p.S187F mutation enhanced the repressive effect (0.318 ± 0.018 versus 0.564 ± 0.048, p  < 0.01). A real‐time polymerase chain reaction confirmed that p.S187F mutation of ANKRD1 decreased the expression of endogenous ANF (0.85 ± 0.05 versus 0.61 ± 0.04, p  < 0.01). Furthermore, nuclear localization experiments demonstrated that the mutation significantly decreased the nuclear distribution of ANKRD1 . Conclusions: The present study is the first to identify the p.S187F mutant of ANKRD1, which is associated with cardiac septal defects.